PENGARUH PELAYANAN PRIMA WAITER TERHADAP KEPUASAN TAMU DI THE ZONA COFFEE BAR & FOOD TALUK KUANTAN - Rahman, Alfahrur; ', Etika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Customer satisfaction is a key to a successful business. There is some factor that impact the customer satisfaction. One of them is the service. To gain customer satisfaction we need to give an excellent service. The purpose of this research is to look how far service excellence impact the customer satisfaction in The Zona Coffee Bar & Food Taluk Kuantan. This research is taking place from March until April 2024 at The Zona Coffee Bar & Food Taluk Kuantan. There are 100 samples that have been chosen randomly (accidental sampling). The data in this research has been collected with questionnaire, observation, and interview. The design of this research is quantitative descriptive that has been processed using SPSS 21. The result of this research shows that there is a positive and significant impact between service excellence (X) on customer satisfaction (Y). Keyword: Service Excellence, Customer Satisfaction, Cafe